Evaluation of Culminating B.Tech Project (CBP) Using Assessment Rubrics and Mapping - Jagtap, Amol M.; Powar, Avinash A. (Journal of Engineering Education Transformations, 2016)
Culminating B.Tech project (CBP) is an Essential and Crucial part of every engineering Student. The main purpose of these culminating projects is to explore the knowledge which is acquired by the student during their studies in whole academic semesters. Students show there capacity and Proficiency by solving the real world and research problems. Outcome-based education (OBE) is an educational theory that bases each part of an educational system around goals (outcomes). By the end of the educational experience, each student should have achieved the goal. The goal of this education was to present the knowledge and skills of an older generation to the new generation of students, and to provide students with an environment in which to learn. So the activities should be well organized, planned and continuously improved. We adopted OBE in our curriculum and for the course on project work we have written course outcomes (CO) i.e. at the end of the course the student should be able to satisfy these objectives and they are mapped with the program outcomes (PO). This paper presents a approach for the outcome-based evaluation of engineering culminating project carried by Final Year Students. The evaluation and assessment is carried out on the basis of rubrics written for each phase of the process. The progress of the each phase is assessed by evaluation team and the guide using the assessment mapping which is based on rubrics. Rubrics mapping covers all the inputs for the assessment of each phase. Mapping of CO to PO is done based on these attributes. Percentage of attainment of each objective and outcome are calculated.